Towards Understanding and Fixing Upstream Merge Induced Conflicts in Divergent Forks: An Industrial Case Study - Sung, Chunhga; Lahiri, Shuvendu; Choudhury, Pallavi; Kaufman, Mike; Wang, Chao (The 42nd International Conference on Software Engineering (ICSE SEIP Track), Seoul, Korea, May 2020, 2020)
Divergent forks are a common practice in open-source software development to perform long-term, independent and diverging development on top of a popular source repository. However, keeping such divergent downstream forks in sync with the upstream source evolution poses engineering challenges in terms of frequent merge conflicts. In this paper, we conduct the first industrial case study of the implications of frequent merges from upstream and the resulting merge conflicts, in the context of Microsoft Edge development. The study consists of two parts. First, we describe the nature of merge conflicts that arise due to merges from upstream and classify them into textual conflicts, build breaks, and test failures. Second, we investigate the feasibility of automatically fixing a class of merge conflicts related to build breaks that consume a significant amount of developer time to rootcause and fix. Towards this end, we have implemented a tool MrgBldBrkFixer and evaluate it on three months of real Microsoft Edge Beta development data, and report encouraging results